La “funzione autoriale” tra lotta politica e branding. Alcuni aspetti dei casi Wu Ming e Scrittura Industriale Collettiva (Altre Modernità, 2018)
The essay aims to explore the potentialities of collective writing for the deconstruction of the authorship in a cultural and political sense. Some historical experiences of collective writing from the avant-gardes are in fact cited in Roland Barthes’essay which, in a dialogue with Michel Foucault, opened in 1968 the debate on “The Death of the Author”; and even if the two scholars came to divergent outcomes as to the diagnosis of the author’s health, both reflections were based on the assumption of the political implications inherent in the figure of the Author as it was built and mythologized by the bourgeois society.It will be seen how, from the end of the twentieth century, some collective writing experiences, in particular the Italian collectives Wu Ming and Scrittura Industriale Collettiva, have attempted to force and deconstruct the authorship by transforming collective writing into a tool of political and cultural struggle. However, the authorship remains unavoidable both for the aesthetic needs of literary criticism and for the commercial exploitation of the publishing market, which transforms this name into a brand to sell; the essay therefore intends to show that collective writing can not in itself be an antidote to the marketing of the author unless it is accompanied by paratextual strategies and extra-literary activities that are truly capable of deconstructing the mythology denounced by Barthes.